CD8+DR+ T-Cells and C3 Complement Serum Concentration as Potential Biomarkers in Thrombotic Antiphospholipid Syndrome. (29th May 2014) - Sarmiento, Elizabeth; Dale, Jonathan; Arraya, Mauricio; Gallego, Antonio; Lanio, Nallibe; Navarro, Joaquin; Carbone, Javier
Abstract : Purpose . To assess complement factors and T lymphocyte activation subset abnormalities in patients with thrombotic antiphospholipid syndrome (APS) as potential biomarkers for development of clinical complications. Methods . We assessed C3, C4, factor B concentrations (nephelometry), complement haemolytic functional activity (CH100, radial immune diffusion), and the activation status of CD4+ and CD8+ T-cells (three-colour flow cytometry) in patients with thrombotic APS. Antiphospholipid (aPL) positive patients without APS-related clinical criteria, systemic lupus erythematosus (SLE) patients, and healthy individuals were evaluated as controls. A clinical followup was performed to assess the potential relationship between the immunological parameters and development of APS-related complications. Results . Lower concentrations of C3 and higher levels of CD8+DR+ cells were risk factors for development of APS-related complications during followup, including rethrombosis and neuropsychiatric symptoms. Patients with diagnosed thrombotic APS had significantly lower levels of C3, C4, and CH100 as well as higher percentages of activated CD4+DR+ and of CD8+DR+ T-cells than healthy controls but similar to that observed in autoimmune disease controls. Conclusion . Lower C3 and C4 complement levels and higher percentages of CD8+DR+ T-cells were observed in thrombotic APS patients. The potential role of these abnormalities as biomarkers of clinical outcome warrants further evaluation in a multicenter study.